Quantitative analysis of the extent of heavy-metal contamination in soils near Picher, Oklahoma, within the Tar Creek Superfund Site. (April 2017) - Beattie, Rachelle E.; Henke, Wyatt; Davis, Conor; Mottaleb, M. Abdul; Campbell, James H.; McAliley, L. Rex
Abstract: The Tri-State Mining District of Missouri, Kansas and Oklahoma was the site of large-scale mining operations primarily for lead and zinc until the mid-1950s. Although mining across the area has ceased, high concentrations of heavy metals remain in the region's soil and water systems. The town of Picher, Ottawa County, OK, lies within this district and was included in the Tar Creek Superfund Site by the U.S. Environmental Protection Agency in 1980 due to extensive contamination. To elucidate the extent of heavy-metal contamination, a soil-chemistry survey of the town of Picher was conducted. Samples ( n = 111) were collected from mine tailings, locally known as chat, in Picher and along cardinal-direction transects within an 8.05-km radius of the town in August 2015. Samples were analyzed for soil pH, moisture, and metal content. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analyses of 20 metals showed high concentrations of lead (>1000 ppm), cadmium (>40 ppm) and zinc (>4000 ppm) throughout the sampled region. Soil moisture content ranged from 0.30 to 35.9%, and pH values ranged from 5.14 to 7.42. MANOVA of metal profiles determined that soils collected from the north transect and chat were significantly different ( p < 0.01) than other sampled directions. Lead, cadmium and zinc were correlated with one another. These data show an unequal distribution of contamination surrounding the Picher mining site. Mapping heavy-metal contamination in these soils represents the first step in understanding the distribution of these contaminants at the Picher mining site. Graphical abstract: Highlights: Abandoned mine wastes continue to release heavy-metals in soils. Concentrations of Pb, Zn, and Cd in soils vary greatly throughout the Picher Minefield. Differential spread of contaminants at the Tar Creek Superfund Site.